Sub-standard ships and human costs of piracy : the case of Captain Prem Kumar - Bateman, Sam (2012)
The human costs of piracy off the Horn of Africa are mounting with an escalating level of violence and shipowners unwilling to pay higher ransoms while operating sub-standard ships. As the plight of Captain Prem Kumar demonstrates, innocent seafarers suffer most.